Response of Cell Walls of Escherichia coli to a Sudden Reduction of the Environmental Osmotic Pressure - Bayer, M. E. (1967)
The rate of survival after osmotic shocks was found to be dependent on the state of growth. When growing logarithmically, Escherichia coli was about 20 to 100 times more sensitive to an abrupt decrease of the environmental osmotic pressure than when it was in the stationary phase. Subjecting rapidly growing cells to such a treatment caused fingerlike extrusions to emerge from the bacterial wall. Our results suggest that underneath these extrusions the rigid layer of the wall contains weak areas which appear as discontinuities or gaps when viewed in an electron microscope. After exposure to osmotic shock, the gaps became wider. We concluded that the gaps represent sites of mucopolymer synthesis where the rigid structure has temporarily been opened by hydrolytic enzymes to allow for the insertion of new wall material into the older portions of the wall.